Analisis portofolio terhadap expected return dan risk saham dengan menggunakan model indeks tunggal (studi kasus pada perusahaan lq 45 yang terdaftar di bursa efek indonesia tahun 2014) - Dwi S, Hendrawan, Dra. W. Mukharomah, MM (2016)
This study aimed to analyze the portfolio against the expected return and risk stocks using single index model case studies on companies LQ 45 listed in the Indonesia Stock Exchange in 2014. Based on the results of this study are expected to provide information to prospective nvestors to invest into stock companies which has the maximum expected return and risk minimal stock. Data of this research is quantitative research in the form of figures obtained from observational data stocks from financial statements gathered from several stages of time and data collected from the companies listed in Indonesia Stock Exchange period of 2014. Based on the survey results revealed that stocks that form the optimal portfolio LQ 45 company listed on the Indonesia stock Exchange, namely shares of PT. Unilever Indonesia Tbk, PT. Media Nusantara Citra Tbk, and PT. Bank Rakyat Indonesia (Persero) Tbk.